40.3k views
4 votes
If f(x)=3^x+10x and g(x)=4x-2, find (f+g)(x)

User Mike Roll
by
5.5k points

2 Answers

7 votes
Hi there!

(f + g)(x) = f(x) + g(x)

(f + g)(x) = (3ˣ + 10x) + (4x - 2)

(f + g)(x) = 3ˣ + 10x + 4x - 2

(f + g)(x) = 3ˣ + 14x - 2

~ Hope it helps!

User Gpupo
by
5.4k points
1 vote
Hi there!

First we need to remember the following.

(f + g)(x) = f(x) + g(x)

Now substitute both of the formulas.

(f + g)(x) = ({3}^(x) + 10x)+ (4x - 2)

Work out the parenthesis.

(f + g)(x) = {3}^(x) + 10x + 4x - 2

And finally collect terms.

(f + g)(x) = {3}^(x) + 14x - 2

~ Hope this helps you!
User Trauer
by
4.6k points